(untitled) (Quinto Sol, 2019)
The aim of this article is to rethink some of the well-established notions regarding Argentinian clandestine detention centers, especially those with an almost exclusive focus on repression as destruction, at the expense of other aspects. This survey places emphasis on other complex forms of repression that, without questioning the role of victims and victimizers nor destruction as an aim, render necessary a more thorough analysis of the phenomenon of clandestine repression. To this purpose, this article takes the clandestine detention center located in ESMA (Navy Mechanics School) during the military dictatorship (1976-1983) as a case study. This center featured a number of specific operational dynamics that were further developed with a considerable degree of autonomy, but which were not exclusive, and so can be observed in other detention centers, though at a minor scale. These dynamics, which reflect more complex manifestations of the repressive apparatus and have so far been understudied, are here presented as follows: a) The particular experience of the “recovery” of prisoners; b) the relationships between practices and repressive crimes and their political extension at a national and international level; and c) financial crime in the context of political repression.